The Camel Site reliefs – an investigation of the site’s original layout and use - Guagnin, Maria; Charloux, Guillaume; Stewart, Mathew; Mora, Pascal; Alsharekh, Abdullah; Hilbert, Yamandù; Groucutt, Huw; al-Qaeed, Ahmed; AlAli, Yasser (Proceedings of the Seminar for Arabian Studies, 2023)
The Camel Site, near Sakākā, is a monumental rock art site in northern Arabia with 20 life-sized reliefs of camels and equids. A chronological assessment showed that the site was in use in the 6th millennium BCE, and was repeatedly revisited over a prolonged period, perhaps spanning several centuries. Using aerial photography and 3D models, we reconstructed the original layout of the site. Our results show that the site was likely designed to be approached via one of two main viewpoints that allowed maximum visibility of the reliefs, and that the location of individual reliefs was chosen for best visibility in the afternoon sun. Reliefs were carved across two tiers, up to a height of ca. 9 m, giving the site a monumental character. Analysis of individual reliefs, including the use of high-resolution 3D models of eroded reliefs, shows that the reliefs can be grouped by stylistic/technological criteria, and that styles changed over time. Reliefs of equids may be linked to a Pre-Neolithic tradition of depicting wild equids in the rock art. Faunal remains recovered at the site included remains of equids found alongside lithic artefacts and beads of various materials. Evidence for possible on-site processing and cooking of equids suggest that the symbology of equids, and perhaps camels, likely extended beyond their depiction in the reliefs.